KEBIJAKAN NASIONALISASI PERUSAHAAN MINYAK SWASTA VENEZUELA PADA MASA PEMERINTAHAN HUGO CHAVEZ - Achmad Syai Lubis (2012)
The courage and firmness Hugos Chavez as president of Venezuela in inhibiting the role of neo-liberalism by way of nationalization is a very interesting thing to investigate. The purpose of Hugo Chavez nationalized the oil companies in Venezuela Swwasta subject will be discussed in this paper. And will be traced by using the concept of National Interest and the Theory of dependence Venezuela was first discovered by Christopher Columbus in 1948 On the second voyage. For years this country was co